Interleukin‐32 expression is associated with a poorer prognosis in head and neck squamous cell carcinoma. Issue 8 (28th January 2013) - Guenin, S.; Mouallif, M.; Hubert, P.; Jacobs, N.; Krusy, N.; Duray, A.; Ennaji, M.M.; Saussez, S.; Delvenne, P.
Abstract Head and neck squamous cell carcinoma (HNSCC) represent the sixth most common malignancy diagnosed worldwide. Patient's survival is low due the high frequency of tumor recurrence. Inflammation promotes carcinogenesis as well as the formation of metastasis. Indeed, proinflammatory mediators are known to stimulate the expression of specific transcription factors such as Snai1 and to increase the ability of tumor cells to migrate into distant organs. The atypical interleukin‐32 (IL32) was mainly described to exacerbate inflammatory responses in rheumatoid arthritis and inflammatory bowel diseases. IL32 is expressed in various cancers but its role in HNSCC physiology is still unexplored. Here, we analyzed the expression of IL32 and its implication on HNSCC aggressiveness. We showed that patients with tumor expressing high amounts of IL32 exhibit decreased disease‐free periods (20.5 mo vs. 41 mo, P = 0.0041) and overall survival (P = 0.0359) in comparison with individuals with weak IL32 tumor expression. This overexpression was negatively correlated with gender (P = 0.0292) and p53 expression (P = 0.0307). In addition, in vitro data linked IL32 expression to metastasis formation since IL32 inhibition decreased Snai1 expression and tumor cell migration in a Boyden chamber assay. Our data provide new insight into the role of IL32 in HNSCC aggressiveness. © 2013 Wiley Periodicals, Inc.